Local government strategies to achieve SDGs social development: governance policy of stunting mitigation in Bantaeng regency, Indonesia - Saharuddin, Saharuddin; Irwan, A. Lukman; Rahmatullah, Rahmatullah; Djalil, Abd. Rasyid; Saputra, Irwan Ade; Irwan, A. Ilmi Utami; Makalew, Amos Shifrieth (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
Stunting has become a global and national issue in recent years, nationally the government in the 2020-2024 National Medium Term Development Plan targets the stunting prevalence rate in Indonesia to decrease to 14% while Bantaeng Regency sets 14.5 percent where the previous year was 22.1%. Stunting is one of the indicators in the Sustainable Development Goals (SDGs), namely the second goal of ending hunger, achieving food security and good nutrition, and promoting sustainable agriculture. The purpose of this research is to look at the implementation of stunting prevention policies using the SDGs approach, local government strategies, and the challenges of implementing stunting prevention policies using Edwards' theory. This research uses descriptive qualitative research methods through direct interviews with all stakeholders who play a role in stunting prevention, documentation, and direct observation or observation. While the data analysis uses an approach according to (Miles et al., 1994), including data collection, data reduction, data presentation, and drawing conclusions. Based on the researcher's findings that the implementation of stunting prevention policies with the SDGs approach from the economic, social, and environmental aspects, while the local government strategy in overcoming stunting is cooperation between regional apparatus, specific and sensitive interventions, while the challenges of implementing stunting prevention policies include communication, resources, disposition, and bureaucratic structure have been implemented, but are still facing various challenges in all aspects of policy implementation.